Enhancement of production, income and employment generation through Integrated Farming System - Singh, R. K.; Tripathi, Uttam Kumar (Indian Farming, 2018)
Over all above discussed system will help farmers to achieve moreincome and overcome from poverty. Popularity of this technology willincrease day-by-day among the farming community in Panna district.The long-term impacts of this technology on eco-friendly foodproduction, natural resources (land and water) and linkages with poverty alleviation should be further explored. The participatory research at farmers’ field could play pivotal role in technology improvements and dissemination.